AB0075 MTOR: An Unexpected Role on the TNF-Regulated MRNA Transcriptome in Rheumatoid Fibroblast-Like Synoviocytes. (9th June 2015) - Karonitsch, T.; Dalwigk, K.; Herdy, B.; Kandasamy, K.; Niederreiter, B.; Holinka, J.; Sevelda, F.; Bilban, M.; Smolen, J.; Kiener, H.; Superti-Furga, G.
Abstract : Background: Accumulating evidence supports the concept that resident mesenchymal cells, namely fibroblast-like synoviocytes (FLS) actively participate in the destructive, inflammatory process of rheumatoid arthritis (RA). FLS maintain a synovial microenvironment that helps to recruit, retain, and activate immune cells, resulting in chronic inflammation with attendant joint destruction. Here, we provide evidence that the mechanistic target of rapamycin (mTOR), which has evolved as a major factor for the maintainance of tissue homeostasis and function, is a critical component of the inflammatory process in synovitis. Results: Immunohistochemical studies revealed that mTOR is activated in rheumatoid synovitis, particularly in FLS of the hyperplastic synovial lining. By using western blot or advanced cell biological methods, such as a recently described synovial organ culture system, we demonstrate that the proinflammatory cytokine TNF activates the mTOR pathway in FLS. To further define the biological significance of these findings, we made use of genome-wide expression profiling. Remarkably, this analysis revealed a so far unknown modulatory role for mTOR in the gene expression programs induced by TNF. Specific inhibition of mTOR by Torin-1 or PP242 increased the TNF-induced expression of genes, known to be regulated by the transcription complex NFkB (e.g. PTGS2, IL8, CCL20). By contrast, FLS treatment with Torin-1 or PP242 diminished the TNF-mediated induction of interferon regulated genes (IRGs), including TNFSF10, CXCL11 and TNFSF13B (BAFF). Conclusions: In conclusion, these studies provide insight into determinants of the synovial tissue response to inflammation and suggest a multifaceted regulatory role for mTOR in synovial inflammatory processes. Disclosure of Interest: None declared